Climate Changes in Africa: Does Economic Growth Matter? A Semi-parametric Approac - Awad, Atif; Mohammed Hersi Warsame, Mohammed Hersi (International Journal of Energy Economics and Policy, 2017)
This study attempts to further examine the impacts of income on carbon emissions in the African continent through investigation of the existence of an Environmental Kuznets Curve (EKC). Within the Stochastic Impacts by Regression on Population, Affluence and Technology (STIRPAT) framework, this is the first study in Africa to explore the income-carbon emissions nexus; using panel data together with a semi-parametric panel fixed effects regression. Our data set refers to a panel of 54 countries in Africa; spanning the period 1990 - 2014. Our results show evidence in contrast to the EKC hypothesis. Our findings shed new light on the income - CO2 emissions nexus and supports implementation of certain policies. Keywords: Per capita income, carbon emissions, STIRPAT environmental Kuznets curve, African continent JEL Classifications: Q01, Q28, Q51, Q52